The LightTyper high-throughput genotyping using fluorescent melting curve analysis - Bennett, C D (BioTechniques, 2003)
Instrumentation, chemistry, and software for high-throughput genotyping using fluorescent melting curves are described. The LightTyper system provides post-amplification genotyping within 10 min using samples in 96- or 384-well microplate formats. The system is homogenous because all reagents are added at the beginning of the reaction and there is no sample manipulation between amplification and genotyping. High-resolution melting curves are achieved by slow and steady heating. As samples are heated, panels of blue light-emitting diodes excite the probes, and fluorescence emission is acquired with a cooled charge-coupled device camera. A variety of probe chemistries are compatible for genotyping on the LightTyper, including dsDNA dyes, single-labeled probes, and fluorescence resonance energy transfer systems. Genotyping is performed automatically, and each sample is given a score reflecting the similarity of the genotype to the standards provided. Standard genotypes can be selected from within the run or imported from other files. Samples and genotypes can be grouped to allow multiple-allele detection on one or many samples. The utility of the LightTyper is illustrated by genotyping samples for the Factor V Leiden mutation and for mutations in the CFTR gene